Preparation And Characterization Of 4ꞌ-(4,4ꞌ-Isopropylidenediphynyl-1,1ꞌdiyldioxy) Dianiline/ 4,4ꞌ- (4,4ꞌ-Isopropylidenediphenoxy) Bis- (Phthalic Anhydride) Polyimide Nickel Nanocomposites (Bpada-Bapp Pi-Nincs) - Jaji, Nuru-Deen (2023)
This work focusing specifically on the preparation and characterization of the 4ꞌ-(4,4ꞌ-isopropylidenediphynyl-1,1ꞌ-diyldioxy)dianiline/4,4ꞌ-(4,4ꞌ-isopropylidene-diphenoxy) bis- (phthalic anhydride) polyimide nickel nanocomposites (BPADA-BAPP PINiNCs).